Pseudoacetabulum a subtle radiological feature of a chronic dislocated total hip replacement. (8th October 2012) - Odak, Saurabh; Mangwani, Jitendra; Ivory, John
Abstract : We report the presence of an unusual radiological feature of formation of pseudoacetabulum in a chronically dislocated and asymptomatic total hip arthroplasty. An elderly demented patient with a history of recurrent dislocations presented to us after an unwitnessed fall and leg length discrepancy. Radiographs showed a dislocated hip arthroplasty with a well-defined, concentric, radio-opaque shadow around the dislocated femoral head suggestive of a pseudoacetabulum. Previous radiographs revealed formation of heterotopic ossification in the soft tissues surrounding the hip. The dislocated joint was reduced under a general anaesthetic with difficulty. This case highlights the presence of heterotopic ossification and formation of pseudoacetabulum as subtle radiological features of chronic instability and dislocation.